Diseño e implementación de un sistema domótico basado en iot - Tinoco Alejandro, Cristhian Alexander (Machala: Universidad Tëcnica de Machala, 2020)
Home automation is the most popular application within the Internet of Things, it is considered a smart home or Home Automation, to that space where all its devices are interconnected through the internet, hence the concept of Internet of Things, due to Since any electrical device can be connected through the cloud, this allows access to many tools that have been developed over time, such as home automation platforms. Home automation platforms are born due to the lack of standards in the manufacture of home automation devices, this generates that each manufacturer has its own device control system and this makes the user have to acquire devices of the same brand, but this has a solution when integrate a home automation platform within the home automation system, since it works as a server where all home automation devices are incorporated regardless of the manufacturer, and with this to be able to monitor and control the home automation system, with the application of said platform, they open a world of possibilities in terms of system configuration, since it can install tools for many purposes such as: Programming, integration of messaging services, file manager, etc. Home automation goes beyond just connecting smart devices at home, its application can range from houses, buildings to an entire city, this application of the internet of things, every day is gaining space within the technological market, since with the passing of the Acquisition of these devices is easier due to the variety of manufacturers and prices, in addition to its easy use, although it lacks standards it is undoubtedly one of the most favorable applications for humans in terms of improving the quality of life, and much more for people with disabilities who need automation of daily tasks that are difficult for them due to their physical problems. A home automation platform is the perfect complement within a home automation system, since it allows the interoperability of almost all smart devices, in addition to being able to monitor and control them through systems that the user can develop, it also has remote access, this makes it operable from anywhere in the world, you just need a stable internet connection.
La domótica es la aplicación más popular dentro del Internet de las cosas, se considera una casa inteligente o Home Automation, a aquel espacio en donde todos sus dispositivos están interconectados entre sí mediante internet, de ahí sale el concepto de Internet de las Cosas, debido a que cualquier dispositivo eléctrico puede conectarse a través de la nube, esto permite el acceso a muchas herramientas que con el paso del tiempo se han ido desarrollando, como plataformas domóticas. Las plataformas domóticas nacen debido a la falta de estándares en la fabricación de dispositivos domóticos, esto genera que cada fabricante tenga su propio sistema de control de dispositivo y esto hace que el usuario tenga que adquirir dispositivos de la misma marca, pero esto tiene solución al integrar una plataforma domótica dentro del sistema domótico, ya que este funciona como un servidor donde se incorporan todos los dispositivos domóticos sin importar el fabricante, y con esto poder hacer el monitoreo y control del sistema domótico, con la aplicación de dicha plataforma, se abren un mundo de posibilidades en cuanto a configuración del sistema, ya que en esta se pueden instalar herramientas para muchos fines por ejemplo: Programación, integración de servicios de mensajería, gestor de archivos, etc. Domótica va más allá de solo conectar dispositivos inteligentes en el hogar, su aplicación puede ir desde casas, edificios hasta una ciudad entera, esta aplicación del internet de las cosas, cada día va ganando espacio dentro del mercado tecnológico, ya que con el pasar del tiempo la adquisición de estos dispositivos es más fácil debido a la variedad de fabricantes y precios , además de su fácil uso, aunque carezca de estándares es sin duda una de las aplicaciones más favorables para el ser humano en cuanto a mejorar la calidad de vida, y mucho más para personas con discapacidad que necesitan una automatización de las tareas diarias que a estas se le dificultan debido a sus problemas físicos. Una plataforma domótica es el complemento perfecto dentro de un sistema domótico, ya que esta permite la interoperabilidad de casi todos los dispositivos inteligentes, además de poder monitorearlos y controlarlos a través de sistemas que el usuario puede desarrollar, también cuenta con acceso remoto, esto lo hace operable desde cualquier parte del mundo, solo necesita una conexión a internet estable.
Keywords: IOT; DOMÓTICA; AUTOMATIZACIÓN; PLATAFORMA DOMÓTICA